Use of Powerbreathe® in inspiratory muscle training for athletes: systematic review - Balbino Rivail Ventura Nepomuceno Júnior; Thaís Borges Gómez; Mansueto Gomes Neto
Abstract Introduction: Inspiratory muscle training (IMT) has been used as part of athletic training. It is beneficial due to an increase in respiratory capacity, and can be related to the optimization of exercise tolerance. There are a growing number of publications on the subject, however the methodological rigor of these publications is still unknown. Objective: To perform a systematic literature review in order to analyze the effects of Powerbreathe® on inspiratory muscle training by athletes. Methods: Original scientific studies published in English, from 2000 to 2015, were included. Their typology was classified. The literature search was performed in the Lilacs, Medline, Pubmed, and Scielo databases using the following keywords: inspiratory muscle training, athletes, and Sports medicine (in English), treinamento muscular inspiratório, atleta, medicina esportiva (in Portuguese). Results: Inspiratory muscle training with specific linear resistance has been used in some athletic training, and its results are promising. However, its application is still recent and generally supported by experiments with limited population and which do not properly define the confounding factors for the results. Conclusion: The state of the art suggests that IMT is useful as a respiratory therapy supporting the training of athletes for some specific sports. However, there is a scarcity of studies of high methodological quality, thus requiring further experiments on the subject.